Heart Failure Syndrome With Preserved Ejection Fraction Is a Metabolic Cluster of Non-resolving Inflammation in Obesity - Tourki, Bochra; Halade, Ganesh V. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure with preserved ejection fraction (HFpEF) is emerging with signs of non-resolving inflammation, endothelial dysfunction, and multi-organ defects. Based on the clinical signs and symptoms, with rise of obesity epidemic HFpEF patients are increased. From recent molecular and cellular study, it becomes evident that HFpEF is not single and homogenous disease but a cluster of heterogeneous pathophysiology with aging as base of the pyramid. Obesity superimposed on aging drives number of inflammatory pathways that intersect with metabolic dysfunction and suboptimal inflammation. Here, we compiled the obesity-directed macrophage dysfunction that coincide with metabolic defects. Obesity-associated pro-inflammatory stimuli facilitates heart and inter-organ inflammation in HFpEF. Furthermore, diversified mechanisms that drive heart failure urge the need of studying omnipresent and unresolved inflammation in animal models to understand HFpEF. This broad and systems-based approach will help to study major translational aspects of HFpEF, since no single animal model recapitulates all signs of differential HFpEF stages in the clinical setting. Here, we covered experimental models that target HFpEF and emphasized the advances of formyl peptide 2 (FPR2) that is important in inflammation-resolution signaling. Dysfunction of FPR2 led to the development of spontaneous obesity, impaired macrophage function, and triggered kidney fibrosis, providing evidence of a multi-organ defects in HFpEF in obesogenic aging experimental model.